NEL, C.M. Inventory of documents - NEL, C.M. (ARCA, 2018)
Government service (Agriculture) at Onderstepoort (1939-1944); Secretary of the Parliamentary Consituencyt Management, Winburg and the Provincial Election Management, Bultfontein; Journal DIE ANTI-KOMMUNIS
COVERAGE 1972; 1 File; 0,11 Metre.
Keywords: NEL, C.M.; Inventories; Politicians; National Party